Childfree Lifestyle Among Indonesian Millennials in the Perspective Maqashid Sharia - Ainun Nuzul, Dinda Amanda; Qolbi, Satria Kharimul; Nugraha, Muhamad Arif; Mawargi, Ega; Fahmiddin, Umair (Hakamain: Journal of Sharia and Law Studies, 2025)
This study examines the childfree lifestyle among Indonesian millennials from the perspective of maqasid sharia within the framework of Islamic family law, with particular attention to the principle of hifz al-nasl. Existing studies on childfree practices have largely focused on sociological change, demographic trends, and individual rights, while limited attention has been given to normative Islamic legal analysis, especially in relation to maqasid sharia, creating a clear gap in contemporary Islamic legal scholarship. This research aims to analyze millennial Muslim perceptions of the childfree lifestyle and to assess how these perceptions align with or challenge the objectives of Islamic family law. The study employs a qualitative normative-empirical legal research approach, combining in-depth interviews with Indonesian Muslim millennials and normative analysis of classical and contemporary Islamic legal sources on family law and maqasid sharia. Informants were selected purposively to represent diverse levels of religious engagement. The findings indicate that most respondents perceive childfree choices as a form of personal autonomy; however, normative tension emerges when such choices are evaluated against the objective of preserving lineage. Respondents with stronger religious commitment tend to view childfree decisions as conditionally permissible or legally problematic, depending on intention and social responsibility. These results demonstrate that the application of maqasid sharia to contemporary family issues remains interpretatively contested and insufficiently contextualized. This research contributes to Islamic legal studies by reaffirming maqasid sharia as a dynamic analytical framework for addressing emerging family law issues among Muslim millennials in Indonesia.